The risks of practicing journalism in Mexico: Analysis of the coverage of the murder of Javier Valdez according to the approach of peace journalism. - Nicolás Gavilán, Maria Teresa (2018)
Violence against journalists in Mexico and especially in the state of Sinaloa has increased its numbers over the years. In this environment is it possible to practice peace journalism proposed by Galtung (2002)? Furthermore, can one report on the violence exercised against journalists with the approach of peace journalism? In this article, the information coverage given to the murder of journalist Javier Valdez Cárdenas was analyzed, a fact that revolutionized journalists and media throughout the country. Through content analysis (Berelson 1952; Krippendorf 1990) the news approaches of 366 news from local newspapers, in its online version, Noroeste and El Debate, and from national ones Reforma and El Universal. The results showed that, in general, the coverage was with a focus towards war journalism.